Sejarah Filsafat; Filsafat Kuno “ Periode Axial” dan Asal-Usulnya - Imron Imron (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2013)
Abstract:Interpreted in Greek philosophy " Philosophia " , commonly translated as the love of wisdom. Root is philos ( philia, love ) and sophia ( wisdom ). According to the original understanding of ancient Greece that philosophy means love of wisdom . But the scope of the original understanding of Sophia was apparently broad. Formerly Sophia means wisdom not only alone but also includes the first truth , vast knowledge, intellectual virtues, healthy consideration to skill artisans and even ingenuity in deciding practical matters. the history of philosophy for world order : the ancient philosophy of " axial period " and the origin of philosophy is its origin in the sixth and fourth centuries BC, during the remarkable development occurs in a large number of separate places all over the Earth. In various areas in the south, north and east of the Mediterranean, in China, India and some parts of them, creative thinkers began to challenge and transcend religious beliefs, and mythology established societies. Thought they were more abstract. Their questions more probing. Their answers more ambitious, more speculative, and further angered. They draw the disciples and followers. They form a school, worship. They are " the philosopher " wisdom seekers, who are not satisfied with simplistic answers and popular prejudices . Keywords : History of Philosophy, Ancient Philosophy, Axial Period